Study the effect of temperature and shear stresses on flow behavior Polylactic acid - polystyrene (PLA/PS) molten mixture - الكاتب هلا; حسن وسوف; فواز الديري (Latakia University Journal -Basic Sciences Series, 2024)
In this research, we have studied the rheological properties of samples of PLA / PS mixtures under the influence of high shear stress and different temperatures, where mixtures were prepared in proportions ranging from 10% to 100%. The mixtures (mixtures) were prepared in preparation for the tests in the viscometer Then study the viscous properties by determining the viscosity and viscous activation energy (E) at constant shear stress, constant shear rate and through Newton’s index (n). The real viscosity transformations were also studied in terms of the inverse of temperature to determine the activation energy at constant shear stresses and constant shear speed, as the activation energy is useful in determining the sensitivity of the polymer’s viscosity to temperature change. The elastic properties of the studied mixtures were also studied using Barus technology, and it was found that the rate of swelling increases with the increase in shear stress, and it was found that there is no significant effect on the swelling coefficient B.